Penerapan Tindak Pidana Malpraktik Yang Menyebabkan Kematian Berdasarkan Uu No.36 Tahun 2009 Tentang Kesehatan - Dwi Fahri Wijaya; Marwin Sitinjak; Aston Martin Panggabean (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The study aims to know of the implementation of criminal sanctions against the establishment of health act no. 36 years 2014 on health care guidelines against the legal policy against malpractice crimes committed by doctors in the practice of malpractice, and the professional sanction given to doctor vang commits a malpractice that causes death. Vang research method used in this study is the conservative vuridis approach to examining secondary data by searching through laws used in malpractice crimes. This research is the answer to the background of the problems associated with malpractice that Causing death under statute no.36 years 2009 about Health. Malpractice is an offense (intentional, dolus, opzettelijk) or negligence in violation of the law, the enforcement of criminal penalties against health powers by law: the 36-year 2014 law on health power consists of prison crime and penal penalties in accordance with the type of ACTS committed by health workers.